Implementasi e-Government dalam Pelayanan Administrasi di Dinas Pemberdayaan Masyarakat Desa Kabupaten Bandung Barat Tahun 2024 - Atik Rochaeni; Noer Apptika Fujilestari; Tinda Irawaty (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2024)
This research aims to evaluate the implementation of E-government in administrative services at the West Bandung Regency Village Community Empowerment Service. Even though local governments have regulations that support the implementation of E-government, initial observation results show that implementation is still not optimal. The village community is still not familiar with E-government and the official website which is still under maintenance is the main obstacle. This research uses a qualitative approach with data collection techniques through in-depth interviews, observation, and literature study. The research results show that the main obstacles to implementing E-government are the low connectivity and use of information technology, lack of competent human resources, and minimal budget allocation. As a result, people have difficulty accessing public services online.